A Novel Pyrimidin-Like Plant Activator Stimulates Plant Disease Resistance and Promotes Growth - Sun, Tie-Jun; Lu, Yun; Narusaka, Mari; Shi, Chao; Yang, Yu-Bing; Wu, Jian-Xin; Zeng, Hong-Yun; Narusaka, Yoshihiro; Yao, Nan (PLOS ONE, 2015)
Plant activators are chemicals that induce plant defense responses to a broad spectrum of pathogens. Here, we identified a new potential plant activator, 5-(cyclopropylmethyl)-6-methyl-2-(2-pyridyl)pyrimidin-4-ol, named PPA (pyrimidin-type plant activator). Compared with benzothiadiazole S-methyl ester (BTH), a functional analog of salicylic acid (SA), PPA was fully soluble in water and increased fresh weight of rice (Oryza sativa) and Arabidopsis plants at low concentrations. In addition, PPA also promoted lateral root development. Microarray data and real-time PCR revealed that PPA-treated leaves not challenged with pathogen showed up-regulation of genes related to reactive oxygen species (ROS), defenses and SA. During bacterial infection, Arabidopsis plants pretreated with PPA showed dramatically decreased disease symptoms and an earlier and stronger ROS burst, compared with plants pretreated with BTH. Microscopy revealed that H2O2 accumulated in the cytosol, plasma membrane and cell wall around intracellular bacteria, and also on the bacterial cell wall, indicating that H2O2 was directly involved in killing bacteria. The increase in ROS-related gene expression also supported this observation. Our results indicate that PPA enhances plant defenses against pathogen invasion through the plant redox system, and as a water-soluble compound that can promote plant growth, has broad potential applications in agriculture.